Seeking for sensory differentiated olive oils? The urge to preserve old autochthonous olive cultivars - Rodrigues, Nuno (2018)
Mediterranean olive heritage richness is poorly characterized. Olive oils from minor cultivars of Northeast- Portugal (Lentisca, Madural, Rebolã, Redondal, Verdeal and Verdeal Transmontana) from centenarian trees were chemical and sensory characterized, aiming to identify autochthonous cultivars capable of producing differentiated olive oils. All oils, produced during two campaigns, were classified as extra virgin. Cv. Redondal showed the highest oxidative stability (OS), total phenols, vitamin E and C18:1/C18:2. Contrary, cv. Madural presented the lowest OS and C18:1/C18:2 ratios, supporting the importance of fatty acids on OS, while cv. Verdeal had the lowest total phenols and vitamin E contents. Sensory notes of tomato, apple, dry fruits, fresh herbs, tomato leaves and cabbage were predominant on the oils of most cultivars, whilst some attributes were more specific, such as banana and kiwi (Madural), cherry and apricot (cvs. Lentisca and Madural). The chemical and sensory diversity enabled the statistical discrimination of all cultivars and harvesting years.